Studi Experimental Terhadap Perpindahan Kalor Pada Tumbukan Multiple Droplets Dengan Variasi Frekuensi Tetesan - Indro Pranoto; Dannys Arif Kusuma; Teguh Wibowo; Fauzun Fauzun; Deendarlianto Deendarlianto; Indarto Indarto (METAL: Jurnal Sistem Mekanik dan Termal, 2018)
The effect of drop frequencies and surface temperature on the maximum spreading ratio, heat transfer rate and heat transfer coefficient of convection have been studied experimentally. The experiments were carried out by investigating different values of drop frequencies at 250, 400 and 600 drops/minute. The surface material of stainless steel with a temperature range of 120°C to 200°C was used in the study. An image processing technique was used to measure the diameter of droplets that were captured by using a high-speed camera. The results of the study show that by increasing frequency of drops has improved significantly the maximum spreading ratio, heat transfer rate and heat transfer coefficient of convection. The results also shown that by increasing the drop frequency has increased accordingly the droplet contact with the surface. It was found that, at higher surface temperature has contributed to the increase of the heat transfer rate and convection heat transfer coefficient. This study suggest that the peak and wetting limit conditions has occurred at the surface temperature of 180°C.